(untitled) (Bangladesh Journal of Child Health, 2021)
Nephrotic syndrome is a common renal problem in children. But it is an uncommon complication for cyanotic heart diseases. It has been rarely reported in pediatric population with congenital cyanotic heart disease in Bangladesh. We found two cases of congenital cyanotic heart disease those were referred to investigate for nephrotic range of proteinuria. Bangladesh J Child Health 2020; VOL 44 (3) :178-180